2008
DOI: 10.1111/j.1095-8649.2007.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Sardine early survival, physical condition and stress after introduction to captivity

Abstract: The main factors that affect early survival, physical damage and stress reactions of sardine Sardina pilchardus after live capture and introduction to captivity were examined. A total of 2800 sardines were captured alive from commercial purse seiners in five trials off southern Portugal and monitored for 4 weeks in aquaculture tanks. Survival rates varied considerably between trials (from <20 to >80% after a month), with most deaths occurring in the first 5 days. Sardine early survival was affected by factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 30 publications
5
39
0
Order By: Relevance
“…Miranda et al (1992), Silva and Miranda (1992) and Marcalo et al (2008) also reported very low survival during the first feeding experiments on sardine larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miranda et al (1992), Silva and Miranda (1992) and Marcalo et al (2008) also reported very low survival during the first feeding experiments on sardine larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory experiments using wild sardine specimens have dealt with acclimation to captive conditions (Marcalo et al 2008), induction to spawning (Olmedo et al 1990), embryonic development (Miranda et al 1990) and larval rearing (Blaxter 1969, Silva and Miranda 1992. Garrido et al (2007Garrido et al ( , 2008 described both the feeding behaviour of sardines under culture conditions, and the diet and food intensity in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a limited number of studies assessing the response of blood parameters of marine pelagic and schooling species to stressful conditions. For instance, Marçalo et al (2006Marçalo et al ( , 2008 found that the European sardine (Sardina pilchardus) exhibited increasing cortisol and glucose levels after being exposed to purse seine fishing and captivity.…”
Section: Introductionmentioning
confidence: 98%
“…Higher density in the net could also explain the higher mortality of herring and South American pilchard after purse seining and net burst (Misund and Beltestad, 1995) or slipping (Mitchell et al, 2002) rather than after purse seining alone, likely due to the high density in the net prior to net burst or slipping. With regard to species composition in the net, mortality of sardine was lower when only sardine were caught than when other species were caught as well (Marçalo et al, 2008).…”
Section: Explanatory Variables For Mortality In Purse Seinesmentioning
confidence: 92%
“…A larger change in water temperature resulted in higher mortality of sardine (Marçalo et al, 2010(Marçalo et al, , 2008. Longer fishing duration resulted in higher mortality of chinook salmon (Candy et al, 1996), mackerel (Lockwood et al, 1983), sardine (Marçalo et al, 2010) and herring .…”
Section: Explanatory Variables For Mortality In Purse Seinesmentioning
confidence: 99%